Medial lower leg perforators: An anatomical study of their distribution and characteristics. Issue 4 (6th June 2016) - Hupkens, Pieter; Westland, Pèdrou B.; Schijns, Wendy; van Abeelen, Marjolijn H.A.; Kloeters, Oliver; Ulrich, Dietmar J.O.
Abstract : Purpose: The integument of the medial lower leg is underestimated as a donor site for local and distant reconstructions. Comprehensive knowledge of its perforator anatomy is lacking. This study aims to determine perforator location and characteristics and to compare these regarding the proximal, middle and distal third of the medial lower leg. Materials and Methods: The medial lower leg region (MLLR) of 16 cadavers was delineated and investigated after injecting the popliteal artery with acrylic paint. Following dissection, all perforators larger than 0.3 mm were localized and mapped. Their course, source vessel, length and diameter were subsequently documented. Results: Overall, 122 perforators were found, 102 (83.6%) originating from the posterior tibial artery, 16 (13.1%) from the medial sural artery and 4 (3.3%) from the anterior tibial artery. A mean of 7.6 ± 2.4 perforators (range 4–13) per MLLR was found. Most perforators (42.6%) were localized in the distal third of the MLLR, followed by the middle (36.9%) and proximal third (20.5%). The largest and longest perforators were found in the proximal third of the MLLR (diameter 1.4 mm, length 9.1 cm), followed by the middle and distal third respectively. Of all musculocutaneous perforators, the majority (78.6%) was located in the middle third of the MLLR. Of all septocutaneous perforators, most (55.3%) were found in the distal third of the MLLR. A small number of unexpected anatomical variants were found. Conclusion: In each third of the MLLR different perforator characteristics were found. Knowledge of these characteristics can be used to direct the reconstructive plan. © 2016 Wiley Periodicals, Inc. Microsurgery 37:319–326, 2017.